Willa's beast eaudiobook - Dixon, Ruby (Icehome, 2019)
Beast. Creature. Monster. Dangerous. All of these things have been said about Gren. Willa doesn't believe it, though. She knows that monsters can sometimes come in appealing packages. She knows that for all of his snarls and fearsome appearance, he'd never hurt her. And she knows she has to get Gren away from the Icehome camp, because no one will ever see him as a person, not when he attacks all who come close. Not when he's tied and treated like an animal. She's going to save him . . . or fall in love. Maybe both. Willa doesn't mind that he's a beast, as long as he's her beast. Contains mature themes.